Integrated learning in a drug and alcohol university degree for Aboriginal and Torres Strait Islander adults: a case study. (March 2019) - Lee, KS Kylie; Harrison, Michelle; Wilson, Scott; Miller, Warren; Perry, Jimmy; Conigrave, Katherine M.
Aboriginal and Torres Strait Islander (Indigenous) health professionals working in the alcohol and other drugs field perform a complex role in tackling substance misuse and related harms. Professional training and development opportunities for these "frontline" Indigenous alcohol and other drugs staff is key to prevent burnout and to allow them to work to their full potential. However, there are many barriers for those seeking to improve their skills. A number of teaching approaches have been described as important, but we were unable to identify peer-reviewed publications that detail the optimal approach to tailor university learning to meet the needs of Indigenous alcohol and other drugs health professionals. This article reflects on the experience of providing one such programme: a graduate diploma in Indigenous health and substance use, designed and delivered specifically for Aboriginal and Torres Strait Islander mature-aged students.